Photocatalytic and eletrocatalytic activity of black TiO2 nanotube arrays by aluminothermic reduction. (11th November 2022) - Li, Bingchen; Jiang, Ying; Liu, Jiaming; Hui, Kezhen; Guo, Limin
Abstract: The black TiO2 nanotubes arrays were prepared by anodizing and aluminothermic reduction process. The prepared samples were characterized by X‐ray diffraction (XRD), SEM, UV‐visible absorption spectroscopy and X‐ray photoelectron spectroscopy (XPS). The photochemical/electrical catalytic activity of the samples before and after blackening treatment was tested. Comparing with the raw TiO2, the macrostructure of the black TiO2 nanotube arrays changes a little, and the tubal walls become a little thicker and rough. The photocatalytic hydrogen production rate has an obvious enhancement (from 8.9 µmol cm −2 h −1 to 22.8 µmol cm −2 h −1 ) after the blackening treatment and the electrocatalytic H2 evolution rate is also improved with a lower onset potential. The increment of trivalent Ti 3+ on the surface is confirmed by XPS and presented by the colour changing of the samples (from white colour to black). The hybrid energy band gap and reduced charge transfer barrier are proved to be essential in promoting the catalytic properties of the black TiO2 nanotube arrays.